2017
DOI: 10.5935/1518-0557.20170057
|View full text |Cite
|
Sign up to set email alerts
|

There is no association between the presence of anti-thyroid antibodies and increased reproductive loss in pregnant women after ART: a systematic review and meta-analysis

Abstract: Women submitted to ART treatments represent a select subgroup of individuals. Several studies have described the relationship between TAI and pregnancy outcomes as a result of ART, with contradictory results. The purpose of this systematic review was to determine the association between TAI and the risk of miscarriage in pregnancies resulting from ART. MEDLINE via PubMed, LILACS and Embase were searched for studies published in peer-reviewed journals from 1999 to 2017. The studies were summarized using the fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
2
16
0
2
Order By: Relevance
“… 54 Interestingly, a similar association of thyroid antibody levels in early pregnancy loss in women undergoing assisted conception techniques has not been demonstrated. 55 , 56 Plowden et al concluded that thyroid antibody (presence of anti-TPO or anti-TG Abs) did not increase risk of pregnancy related complications including subclinical hypothyroidism. 57 However a recent meta-analysis by Busnelli et al adds the possibility of the antibody status impacting on the rate of live birth.…”
Section: Thyroid Disorders In Pregnancymentioning
confidence: 99%
“… 54 Interestingly, a similar association of thyroid antibody levels in early pregnancy loss in women undergoing assisted conception techniques has not been demonstrated. 55 , 56 Plowden et al concluded that thyroid antibody (presence of anti-TPO or anti-TG Abs) did not increase risk of pregnancy related complications including subclinical hypothyroidism. 57 However a recent meta-analysis by Busnelli et al adds the possibility of the antibody status impacting on the rate of live birth.…”
Section: Thyroid Disorders In Pregnancymentioning
confidence: 99%
“…31 % der Frauen, die ein TSH > 2,5 mIU/L hatten, kein Unterschied in der Lebendgeburtrate zwischen der LT4-Gruppe versus der Placebogruppe (55 versus 58 Lebendgeburten) bestand [15]. Auch bei Frauen mit assistierter Reproduktion/In-vitro-Fertilisierung (IVF) wurde der Zusammenhang zwischen Schilddrüsenfunktion sowie TPO-AK und Aborten sowie Lebendgeburten intensiv untersucht [18][19][20][21][22]. In diesem Kontext zeigte ein RCT mit 600 euthyreoten, TPO-AK-positiven Frauen, welche sich einer IVF mit Embryotransfer unterzogen, keinen signifikanten Unterschied in der Lebendgeburt-und Abortrate zwischen einer LT4-Gruppe mit 25 bis 50 μg tgl.…”
Section: Fertilitätunclassified
“…The authors did find a significant association with miscarriage and the presence of anti-thyroid antibodies in direct contrast to the outcome of a recent meta-analysis, which concluded that there was no association. 20 Other recent studies regarding the role of anti-thyroid antibodies and miscarriage have also had conflicting results. 21,22 Currently there is no clear evidence that anti-thyroid antibody positive women with TSH below 4 mU/L are at increased risk of miscarriage.…”
Section: Subclinical Hypothyroidism and Spontaneous Abortionmentioning
confidence: 99%
“…This result does not preclude an association, but it does show the well known TSH cut‐off of 2.5 mU/L is not a discriminator for this outcome. The authors did find a significant association with miscarriage and the presence of anti‐thyroid antibodies in direct contrast to the outcome of a recent meta‐analysis, which concluded that there was no association . Other recent studies regarding the role of anti‐thyroid antibodies and miscarriage have also had conflicting results .…”
Section: Introductionmentioning
confidence: 99%